Mutations of DNAI1 in Primary Ciliary Dyskinesia: Evidence of Founder Effect in a Common Mutation - Zariwala, Maimoona A; Leigh, Margaret W; Ceppa, Franck; Kennedy, Marcus P; Noone, Peadar G; Carson, Johnny L; Hazucha, Milan J; Lori, Adriana; Horvath, Judit; Olbrich, Heike; Loges, Niki T; Bridoux, Anne-Marie; et al. (American journal of respiratory and critical care medicine, 2006)
Primary ciliary dyskinesia (PCD) is a rare, usually autosomal recessive, genetic disorder characterized by ciliary dysfunction, sino-pulmonary disease, and situs inversus. Disease-causing mutations have been reported in DNAI1 and DNAH5 encoding outer dynein arm (ODA) proteins of cilia. We analyzed DNAI1 to identify disease-causing mutations in PCD and to determine if the previously reported IVS1+2_3insT (219+3insT) mutation represents a "founder" or "hot spot" mutation. Patients with PCD from 179 unrelated families were studied. Exclusion mapping showed no linkage to DNAI1 for 13 families; the entire coding region was sequenced in a patient from the remaining 166 families. Reverse transcriptase-polymerase chain reaction (RT-PCR) was performed on nasal epithelial RNA in 14 families. Mutations in DNAI1 including 12 novel mutations were identified in 16 of 179 (9%) families; 14 harbored biallelic mutations. Deep intronic splice mutations were not identified by reverse transcriptase-polymerase chain reaction. The prevalence of mutations in families with defined ODA defect was 13%; no mutations were found in patients without a defined ODA defect. The previously reported IVS1+2_3insT mutation accounted for 57% (17/30) of mutant alleles, and marker analysis indicates a common founder for this mutation. Seven mutations occurred in three exons (13, 16, and 17); taken together with previous reports, these three exons are emerging as mutation clusters harboring 29% (12/42) of mutant alleles. A total of 10% of patients with PCD are estimated to harbor mutations in DNAI1; most occur as a common founder IVS1+2_3insT or in exons 13, 16, and 17. This information is useful for establishing a clinical molecular genetic test for PCD.